A connection based approach to common-sense topological description and reasoning. - Gotts, N.M.; Gooday, J.M. (Monist, 1996)
Explores alternative approaches to region-connection calculus (RCC), which uses a logic-based artificial intelligence approach to formalizing the qualitative description of spatial properties and relations. Point-set and algebraic topology; Limitations of mathematical topology as formalism for qualitative spatial reasoning; Topology based on regions and connection.